2006
DOI: 10.2307/25065642
|View full text |Cite
|
Sign up to set email alerts
|

Adscription of Parafestuca albida (Lowe) E. B. Alexeev to Koeleria Pers.

Abstract: A new name, Koeleria loweana Quintanar, Catalán & Castrov. nom. nov., is provided for Parafestuca albida (Lowe) E. B. Alexeev, the single species of the endemic Madeiran genus created by Alexeev to accomodate Festuca albida Lowe. A lectotype is selected and a first chromosome number of 2n = ca. 175 is reported for this taxon. Careful re‐examination of morphological characters and new chromosome data support the inclusion of this relict Macaronesian lineage within the diploid‐to‐highly‐polyploid complex genus K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…1 and 2). Parafestuca was included in Koeleria, not only because of its placement here, but also because its morphology is typical of the genus Koeleria (Soreng et al, 2003;Quintanar et al, 2006). This mostly perennial lineage also included the Trisetum ovatum group, that comprised the annual T. loeflingianum, T. ovatum, and the small genus Gaudinia, with either strongly contracted panicles (Trisetum representatives) or racemes of spikelets (Gaudinia).…”
Section: Discussionmentioning
confidence: 99%
“…1 and 2). Parafestuca was included in Koeleria, not only because of its placement here, but also because its morphology is typical of the genus Koeleria (Soreng et al, 2003;Quintanar et al, 2006). This mostly perennial lineage also included the Trisetum ovatum group, that comprised the annual T. loeflingianum, T. ovatum, and the small genus Gaudinia, with either strongly contracted panicles (Trisetum representatives) or racemes of spikelets (Gaudinia).…”
Section: Discussionmentioning
confidence: 99%
“…1-3) is in agreement with previous molecular studies (Soreng & al., 1990;Davis & Soreng, 1993;Nadot & al., 1994;Clark & al., 1995;Hsiao & al., 1995aDuvall & Morton, 1996;Catalán & al., 1997;Soreng & Davis, 1998Hilu & al., Fig. 5. Microscopic details from the spikelets of Boissiera squarrosa (a-c) and Bromus erectus (d-f) 1999; Mathews & al., 2000;GPWG, 2001;Hunter & al., 2004;Fernández Souto & al., 2006;Quintanar & al., 2006Quintanar & al., , 2007Soreng & al., 2007;Bouchenak-Khelladi & al., 2008). Both plastid (Fig.…”
Section: 'Core Pooideae'mentioning
confidence: 99%
“…KEYWORDS: Aveneae, grasses, Poaceae, Poeae, Pooideae, ITS, matK gene-3′trnK exon, systematics Compared with information from the chloroplast genome, data from nuclear genomic regions of Pooideae are limited and mainly restricted to the tribes Triticeae and Poeae/Aveneae (e.g., Baum & Appels, 1992;Hsiao & al., 1994Hsiao & al., , 1995aHsiao & al., , b, 1999Kellogg & Appels, 1995;Grebenstein & al., 1998;Mason-Gamer & al., 1998;Mathews & al., 2000;Mason-Gamer & Kellogg, 2000;Mason-Gamer, 2001Röser & al., 2001;Torrecilla & Catalan, 2002;Blattner 2004;Brysting & al., 2004;Catalán & al., 2004;Quintanar & al., 2006Quintanar & al., , 2007Chiapella, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A morphological reexamination and accomplished (Garcia-Jacas et al, 2001; Susanna et new chromosome data suggested inclusion of this al., 2011), but Yunquea has not been included. genus into Koeleria, and this has been further Two genera have been investigated recently and supported by nr TS and cp trnT-F sequences in this submerged into other genera based primarily on other same investigation (Quintanar et al, 2006). Within than molecular data.…”
mentioning
confidence: 70%